Ecosystem roles and conservation status of bioturbator mammals - Beca, Gabrielle; Valentine, Leonie E.; Galetti, Mauro [UNESP]; Hobbs, Richard J. (Wiley, 2022)
The action of biological reworking of soils is referred to as bioturbation, and many species of mammals globally have an important role in soil disturbance, modifying ecosystem characteristics. We examined global patterns in the distribution, conservation status, and threats to the world’s bioturbator mammals and illustrated the relevant roles these species play in ecosystem engineering related to soil processes and services. We searched the data available on 3932 non-flying land-dwelling mammals included in the International Union for Conservation of Nature’s (IUCN) Red List. Using existing literature and online databases, we determined that 869 (22%) of the non-flying land-dwelling mammals accessed can be considered as bioturbators in three distinct groups: foragers (n = 123), semi-fossorial species (n = 652), and strictly fossorial species (n = 94). Of the world’s bioturbator mammal species, 16% are threatened, 2% are already Extinct, and 8% are classified as Data Deficient. Foragers have the highest percentage of threatened (35%) and Extinct (5%) species, while strictly fossorial species have the highest percentage of Data Deficient species (12%). Although the majority of bioturbator mammal species are found in Asia (32%), Oceania is the continent with the highest percentage of threatened (27%) and Extinct (11%) bioturbator species, while Central and South America have the highest percentage of species classified as Data Deficient (24%). The threats experienced by the greatest number of bioturbator mammal species are activities related to agriculture and aquaculture (29%), and biological resource use (22%). Soil bioturbation can improve ecosystem health by reducing soil compaction, increasing nutrient cycling, soil moisture, microbe diversity, plant recruitment, and carbon storage. The loss of bioturbator mammals could trigger cascading effects throughout the ecosystems they inhabit. A better understanding of their conservation status is important so that effective conservation measures can be developed.
Keywords: bioturbation; conservation; digging; ecosystem engineers; ecosystem services; soil disturbance; terrestrial mammals (Mammalia)